Permainan Teka-Teki Silang dalam Pembelajaran Bahasa Indonesia - Jannah, Shakilla Feshtyani Miftahul; Salim, Herli (Didaktika, 2021)
The Corona Virus pandemic in 2019 is commonly known as Covid-19. Indonesia is one of the countries affected by Covid-19. As a result of the Covid-19 pandemic, researchers encountered obstacles when completing research because they could not go directly to the field. Games are one of the activities that are useful for integrating newly acquired words into word placements by students. Cross Puzzle is a game in which we need to fill in the empty space (in the form of a white box) with letters that form a word based on the directions given horizontally and downwards". The qualitative approach is the approach used by researchers in working on this research. For data needs, researchers perform data processing using data sourced from previous journals and theses. The library research method is the method used by researchers in this study. The research technique used by researchers is literature review. This study aims to determine the process of using crossword puzzles in Indonesian language learning. Based on the literature analysis conducted by the researcher, the first result shows that crossword puzzles have a positive effect on the improvement of students' vocabulary mastery skills in learning Indonesian. The second result, shows that through understanding the vocabulary students get better at reading and students no longer have difficulty reading vocabulary. Based on research data, the word game technique is feasible to implement. This situation shows an increase in student creativity and productivity in language skills including listening, speaking, and writing.